Nutraceuticals in Lipid-Lowering Treatment: A Narrative Review on the Role of Chitosan. (May 2015) - Patti, Angelo Maria; Katsiki, Niki; Nikolic, Dragana; Al-Rasadi, Khalid; Rizzo, Manfredi
Lipid-lowering drugs may cause adverse effects and, although lipid targets may be achieved, a substantial residual cardiovascular (CV) risk remains. Treatment with agents mimicking proteins present in the body, such as incretin-based therapies, provided promising results. However, in order to improve lipids and CV risk, lifestyle measures remain important. Some researchers focused on nutraceuticals that may beneficially affect metabolic parameters and minimize CV risk. Chitosan, a dietary fiber, can regulate lipids with benefit on anthropometric parameters. The beneficial properties of dietary supplements (such as green tea extract, prebiotics, plant sterols, and stanols) on plasma lipids, lipoproteins, blood pressure, glucose, and insulin levels and their anti-inflammatory and anti-oxidant effects are documented. However, larger, prospective clinical trials are required to confirm such benefits. Such treatments may be recommended when lipid-lowering drugs are neither indicated nor tolerated as well as in order to achieve therapeutic targets and/or overcome residual CV risk.